2018
DOI: 10.4236/jtr.2018.61005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Delay and Associated Clinical Features of Tuberculosis among Adult Patients with Acute Myeloid Leukemia in Doha, Qatar

Abstract: Background: Tuberculosis is currently the world's leading cause of death arising from a single infectious condition. While T cell mediated immunity is recognized to have a major contribution to tuberculosis activation, the present investigation confirmed that TB was more prevalent among patients with acute myeloid rather than lymphoid leukemia and such association was frequently overlooked. The primary objective of this study is to estimate the diagnostic delay of tuberculosis among patients with acute myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…On the other hand, a meta-analysis supported that all types of cancer increased the risk of active TB infection, with variation in the cumulative incidence rate/100,000 population (CIR) stratified by cancer type and TB incidence, where the CIR in low TB incidence countries being highest in hematological malignancies (418/100,000 population), while that reported in solid cancers was 244/100,000 population [ 19 ]. One study done in Qatar concluded that among 215 subjects with acute myelocytic leukemia identified during the study period, 12 (5.58%) were diagnosed with TB, in comparison to our study which reported no cases in those with hematological malignancies [ 22 ]. This could be justified by the actual higher number of included solid tumor cases in this study compared to the cases with hematological malignancies.…”
Section: Discussioncontrasting
confidence: 81%
“…On the other hand, a meta-analysis supported that all types of cancer increased the risk of active TB infection, with variation in the cumulative incidence rate/100,000 population (CIR) stratified by cancer type and TB incidence, where the CIR in low TB incidence countries being highest in hematological malignancies (418/100,000 population), while that reported in solid cancers was 244/100,000 population [ 19 ]. One study done in Qatar concluded that among 215 subjects with acute myelocytic leukemia identified during the study period, 12 (5.58%) were diagnosed with TB, in comparison to our study which reported no cases in those with hematological malignancies [ 22 ]. This could be justified by the actual higher number of included solid tumor cases in this study compared to the cases with hematological malignancies.…”
Section: Discussioncontrasting
confidence: 81%
“…21 In 2018, a study in Qatar found that approximately 5.58% of 215 patients with acute myelocytic leukemia were coinfected with TB. 22 It is also important to note that our patient was infected with COVID-19 before TB reactivation. The COVID-19 virus was found to lead to multiple histological damages to the lungs, and it could play a significant role in TB reactivation secondary to immunosuppression due to the use of corticosteroids as a course of treatment.…”
Section: Discussionmentioning
confidence: 86%
“…reported that patients with solid malignancies had a 4.5‐times higher risk of TB infection than healthy individuals 21 . In 2018, a study in Qatar found that approximately 5.58% of 215 patients with acute myelocytic leukemia were coinfected with TB 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation